Catalytic cracking of palm oil to gasoline over pretreated Cu-ZSM-5 - Siregar, Tirena Bahnur; Saidina Amin, Nor Aishah (Penerbit UTM Press, 2006)
The catalytic conversion of palm oil to gasoline using hydrogen pretreatment onH-ZSM-5 with different copper loadings is discussed in this paper. The Cu-ZSM-5 catalysts were prepared using incipient wetness impregnation technique. The crystallinity, acidity and surface area were examined by X-ray diffraction (XRD), Pyridine adsorption - infra red spectroscopy (Py-IR), and Nitrogen Adsorption (NA). The results revealed that the crystallinity, acidity, and surface area of catalyst decreased with increasing copper loading. The catalytic testing was carried out in a fixed bed reactor at atmospheric pressure with hydrogen flow rate of 1 L/h for an hour for hydrogen pretreatment on catalysts. Then, the cracking process was continued at 500Â°C and weight hourly space velocity (WHSV) of 2.5 hâ€“1 for four hours. Loading copper on the ZSM-5 catalyst showed adverse effects on catalytic activity. The highest gasoline component was aromatics, which was about 11.45 wt % (all consisted of alkyl benzene) followed by 10.53 wt% of naphthenes and 4.06 wt% of isoparaffins for 6 wt% Cu-ZSM-5. Gas as side product consisted mainly of C3 compounds with 53.30 mol% followed by 29.84 mol% of C4 and 0.62 mol% of C5 compounds.